The specificity of the adaptation difficulties of students with special educational needs in studying in the university - Fedotenko, Inna; Pazukhina, Svetlana (Student Niepełnosprawny. Szkice i Rozprawy, 2019)
The article deals with the problems of psychological and social adaptation of students with special educational needs to studying in the university. Successful adaptation helps the student to accept new requirements, to build positive relationships with teachers and classmates, to actualize motives of self-realization, it develops personal growth. The authors describe the student`s cognitive, motivational, regulatory, communication difficulties; they also identify the main typological groups. As a result of the empirical research four main clusters of students were identified according to the investigated indicators. The leading tactics of assistance to students with special educational needs are described during designing their individual educational routes.